Estimates of Prevalence Rates of Cancer Patients With Children and Well-Being in Affected Children: A Systematic Review on Population-Based Findings - Inhestern, Laura; Bultmann, Johanna Christine; Johannsen, Lene Marie; Beierlein, Volker; Möller, Birgit; Romer, Georg; Koch, Uwe; Bergelt, Corinna (Frontiers in Psychiatry, 2021)
This review assessed population-based estimate rates of cancer patients with minor and young adult children (≤25 years), children and young adults having a parent with cancer as well as the psychosocial situation and well-being of children and young adults affected by parental cancer. 18 publications on population-based studies were included. Studies varied in age ranges of the cancer patients and of the children. The prevalence rates of cancer patients having children ranged from 14% to 22.4% depending on the sample structure (e.g. age, gender). Studies reported that between 1.6% and 8.4% of children and young adult children have a parent with a history of cancer. Seven publications reported on psychosocial situation or well-being in children and young adults affected by parental cancer. Estimate rates of psychosocial problems, psychiatric diagnoses or distress ranged between 2.5% and 34% of children depending on the method of measurement and outcome. The differences in the sample structure between the studies impeded the comparison of prevalence rates. However, the findings help to determine the need for specific support services and health care planning. The results support the importance to routinely include issues on the parental role of patients and questions on the well-being and coping of children into psychooncological care. If necessary, support should be provided to families living with a cancer diagnosis.